Salivary magnesium during pregnancy and labor and its relation to gingivitis - Al-Obaidi, Wesal A. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Changes in the level of salivary magnesium could be of great clinical interest not only because of its relation with oral health but also with the physiological alteration occurring during pregnancy. The aim of this study was to investigate the effect of pregnancy on the salivary magnesium level and their relations to gingivitis.Materials and methods: Salivary samples were taken from 24 pregnant women, 17 non pregnant and 14 lactating women. Flow rate was calculated. The supernatant salivary samples were assayed using atomic absorption spectrophotometer. Gingival Index was applied for the assessment of gingival inflammation.Results: Salivary magnesium concentration was significantly the lowest mean value during pregnancy, with decrease in concentration in the third trimester followed by a marked increase after labor reaching the normal level. Pregnant women had a significantly highest Gingival Index mean than other control groups. Very weak correlations were found between flow rate and (pregnancy and salivary magnesium). A positive correlation was recorded between gingivitis and pregnancy and a negative correlation between gingivitis and salivary magnesium. However, statistically all correlations were not significant.Conclusion: The salivary magnesium is influenced by female sex hormone during pregnancy. Analysis of saliva may be applicable as an investigation means of the physiological alterations that occur during and after pregnancy.